The Protective Effects of α-Mangostin Attenuate Sodium Iodate-Induced Cytotoxicity and Oxidative Injury via Mediating SIRT-3 Inactivation via the PI3K/AKT/PGC-1α Pathway - Chuang, Chen-Ju; Wang, Meilin; Yeh, Jui-Hsuan; Chen, Tzu-Chun; Tsou, Shang-Chun; Lee, Yi-Ju; Chang, Yuan-Yen; Lin, Hui-Wen (Antioxidants, 2021)
It is well known that age-related macular degeneration (AMD) is an irreversible neurodegenerative disease that can cause blindness in the elderly. Oxidative stress-induced retinal pigment epithelial (RPE) cell damage is a part of the pathogenesis of AMD. In this study, we evaluated the protective effect and mechanisms of alpha-mangostin (α-mangostin, α-MG) against NaIO3-induced reactive oxygen species (ROS)-dependent toxicity, which activates apoptosis in vivo and in vitro. MTT assay and flow cytometry demonstrated that the pretreatment of ARPE-19 cells with α-MG (0, 3.75, 7.5, and 15 μM) significantly increased cell viability and reduced apoptosis from NaIO3-induced oxidative stress in a concentration-dependent manner, which was achieved by the inhibition of Bax, cleaved PARP-1, cleaved caspase-3 protein expression, and enhancement of Bcl-2 protein. Furthermore, pre-incubation of ARPE-19 cells with α-MG markedly inhibited the intracellular ROS and extracellular H2O2 generation via blocking of the abnormal enzyme activities of superoxide dismutase (SOD), the downregulated levels of catalase (CAT), and the endogenous antioxidant, glutathione (GSH), which were regulated by decreasing PI3K-AKT-PGC-1α-STRT-3 signaling in ARPE-19 cells. In addition, our in vivo results indicated that α-MG improved retinal deformation and increased the thickness of both the outer nuclear layer and inner nuclear layer by inhibiting the expression of cleaved caspase-3 protein. Taken together, our results suggest that α-MG effectively protects human ARPE-19 cells from NaIO3-induced oxidative damage via antiapoptotic and antioxidant effects.